A Review of the Iron–Air Secondary Battery for Energy Storage. Issue 2 (26th September 2014) - McKerracher, R. D.; Ponce de Leon, Carlos; Wills, R. G. A.; Shah, A. A.; Walsh, Frank C.
Abstract Recent interest in the iron–air flow battery, known since the 1970s, has been driven by incentives to develop low‐cost, environmentally friendly and robust rechargeable batteries. With a predicted open‐circuit potential of 1.28 V, specific charge capacity of <300 A h kg−1 and reported efficiencies of 96, 40 and 35 % for charge, voltage and energy, respectively, the iron–air system could be well suited for a range of applications, including automotive. A number of challenges still need to be resolved, including: efficient and moderate‐cost bifunctional oxygen electrodes, low‐cost iron electrodes able to decrease corrosion and hydrogen evolution, new cell designs using additive manufacturing technologies and mathematical models to improve battery performance. This Minireview considers the thermodynamics and kinetics aspects of the iron–air battery, the operational variables and cell components, thereby highlighting current challenges and assessing recent developments.